Horizontal inequality and data challenges - Carla Canelas; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Inequality and social exclusion receive considerable contemporary policy attention. In the field of international development, inequality - both vertical (between individuals and households) and horizontal (between groups) - is a core concern in the 2030 Agenda for Sustainable Development. Despite considerable attention to horizontal inequality in both research and policy, there are notable gaps and weaknesses in our empirical knowledge about how it manifests within and across countries and over time. This has implications not only for the rigour with which we can build and test theories in this area, but also for informing policy, monitoring trends, and evaluating the impact of interventions. This paper probes what more can be learned from existing survey and census data to address empirical gaps. It argues that key methodological, conceptual, and - in particular - political issues pose persistent challenges for such survey and census data on topics relating to "ethnicity" broadly defined. These challenges imply not only real limits in the so-called data revolution for sustainable development, but also risks to "evidencebased" policy making in this area when it relies too heavily on quantitative data. This paper serves also as the introductory and framing paper for a collection of studies entitled "Horizontal Inequality in the Global South: Data, Measurement, and Trends", to be published in a forthcoming UNUWIDER special issue of Social Indicators Research.
Keywords: J15; I24; D63; C80; 330; ethnic groups; group-based inequality; horizontal inequality; inequality